CSR OF MAHARATNA COMPANIES IN INDIA: A QUEST - Behera, Dr. Bhagabata (IJRDO - Journal of Business Management, 2016)
Business is a creation of the society and must give back to society what it wants. The society comprises of the various stakeholders like shareholders, employees, ustomers, government etc. Management should set example by developing values towards the society. Social responsibility is an important feature of every business in the modern times. Corporate social Responsibility is an increasingly important part of the business environment and its change. The key drivers of this change have been the globalization of trade, the increased size and influence of companies, the repositioning of government and rise in strategic importance of stakeholders relationship, knowledge and brand reputation. In India companies like TATA and Birla are practicing the Corporate Social Responsibility (CSR) for decades, long before CSR become a popular basis. All the activities undertaken in the name of the CSR are mainly philanthropy, or an extension of philanthropy. It seems that CSR in India has been evolving in domain of profit distribution. There is need to increase the understanding and active participation of business in equitable social development as an integral part of good business practices. . Corporate sustainability is an evolving process and not an end. The objective of this study is to measurement of the quantity and quality of voluntary social disclosures in the annual reports or sustainability reports of the companies. The emergence of Sec. 135 of Indian Companies Act 2013 has been given a wider approach to Corporate Social Responsibility (CSR), with companies recognizing that improving their own impacts and addressing wider social and environmental problems will be crucial in securing their long-term success. In this paper an attempt has been made to highlights the issues and challenges faced by the industry in implementing CSR and also study the provision of CSR under the Companies Act 2013 its impact on Indian corporate sector. The study reveals that Indian corporate sectors are spending substantial amounts on CSR activities voluntarily. Primarily, such spending is on development of neighborhood, primary health care, education, safe drinking water etc. in the areas where the businesses are located. But they fail to point out on important changes that are taking place worldwide that could blow the business out of the water. CSR is viewed as vital tool for improving their competitive edge over their rivals.